The smoke in our eyes - Grady, James, 1949- (Pegasus Crime, 2024)
In 1959 Montana, when a fatal car accident shatters his world, 10-year-old Lucas finds himself confronting crime and vengeance, humor and heroism, all against the backdrop of growing up during the Space Race, the brutal racism of segregation and the hope of a new generation to move us forward.